2010
DOI: 10.3201/eid1605.091693
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Tuberculosis Progression

Abstract: To assess the association between vitamin D deficiency and tuberculosis disease progression, we studied vitamin D levels in a cohort of tuberculosis patients and their contacts (N = 129) in Pakistan. Most (79%) persons showed deficiency. Low vitamin D levels were associated with a 5-fold increased risk for progression to tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(174 citation statements)
references
References 12 publications
11
144
3
4
Order By: Relevance
“…Two studies have examined the influence of VDR genotype on response to antimicrobial therapy: Roth et al reported that the FF genotype of the FokI VDR polymorphism and the Tt genotype of the TaqI VDR polymorphism associated with faster sputum culture conversion in a cohort of pulmonary TB patients in Peru (53) , while Babb et al reported no difference in time to sputum culture conversion according to TaqI or FokI VDR genotype among South African TB patients (54) . Recently, a cohort study conducted in Pakistan (55) reported that profound vitamin D deficiency among healthy household TB contacts at baseline associated with increased risk of development of active TB over the subsequent 4 years: seven out of thirty contacts with baseline plasma 25(OH)D <17 . 5 nmol/l developed active TB during follow-up, compared with one of thirty-two with plasma 25(OH)D 17 .…”
Section: Prospective Observational Studiesmentioning
confidence: 99%
“…Two studies have examined the influence of VDR genotype on response to antimicrobial therapy: Roth et al reported that the FF genotype of the FokI VDR polymorphism and the Tt genotype of the TaqI VDR polymorphism associated with faster sputum culture conversion in a cohort of pulmonary TB patients in Peru (53) , while Babb et al reported no difference in time to sputum culture conversion according to TaqI or FokI VDR genotype among South African TB patients (54) . Recently, a cohort study conducted in Pakistan (55) reported that profound vitamin D deficiency among healthy household TB contacts at baseline associated with increased risk of development of active TB over the subsequent 4 years: seven out of thirty contacts with baseline plasma 25(OH)D <17 . 5 nmol/l developed active TB during follow-up, compared with one of thirty-two with plasma 25(OH)D 17 .…”
Section: Prospective Observational Studiesmentioning
confidence: 99%
“…81 The influence of vitamin D on tuberculosis can be traced back to the predrug era, when exposure to sunlight was considered an important adjuvant treatment modality. Yesudian et al hypothesized that high-risk populations latently infected with the organism would develop full-fledged disease upon migrating from an area with high sun exposure to areas with diminished sunlight.…”
mentioning
confidence: 99%
“…In a cohort follow-up study from Pakistan, low vitamin D levels were associated with progression to active TB disease in healthy household contacts. The findings suggested also the higher susceptibility of women to the infection, because of their low socioeconomic status, poor nutrition, traditional/cultural traits, and little exposure to sunlight [52]. In Southeast Asian countries, TB is also a major public health issue.…”
Section: Vitamin D Deficiency and Tbmentioning
confidence: 99%